Analysis of Self Efficacy and Motivation as Contributing Factors in Second Language Acquisition: A Literature Review - Leslie Keith Descipulo Manipol; Nasrullah Nasrullah; Jumariati Jumariati (Universitas Muhammadiyah Kalimantan Timur, 2024)
Several factors are thought to influence second language acquisition (SLA). The concepts of motivation and self-efficacy are frequently linked to SLA success. In terms of linguistic outcomes, motivation is a significant contributor, whereas self-efficacy is a component of social, metacognitive, and cognitive strategies. Students with varying levels of motivation and self-efficacy attribute diverse reasons for their success and failure in learning a second language, so these elements are crucial in determining one's level of success in learning a second language. The purpose of this study is to analyze self-efficacy and motivation as contributing factors to second language acquisition. This paper gathered and reviewed journal articles on motivation and self-efficacy in second language acquisition from a variety of journals in the field using thematic analysis. The method for this study uses a literature review in order to demonstrate the contribution of the factors self-efficacy and motivations to second language acquisition. It is expected that self-efficacy and motivation improve students' learning performance in a variety of language skills. The implications of this study benefit language teachers by helping learners create positive beliefs about themselves and improve their confidence about their abilities to learn a second language.